The development of sharia based micro waqf banks as a form of MSME empowerment - Yasmin, Hanun Aulia; Makrufah, Elita Putri Ayu Nur; Coriawan, Elvaretta Aldora (Universitas Sebelas Maret, 2022)
Poverty is one of the big problems for many countries in the world, both developing and developed countries. Poverty in Indonesia itself has become a prolonged problem that until now has not found a solution. According to data from the Central Statistics Agency or BPS, the percentage of urban poor in Indonesia in September 2020 reached 7.88 percent. This figure increased to 7.89 percent in March 2021. This condition is reversed compared to the number of poor rural people in Indonesia. In September 2020, the percentage of rural poor in Indonesia reached 13.20 percent, but this number decreased to 13.10 percent in March 2021. Seeing these conditions, the government strives to reduce poverty every year with various strategies. One of the strategies implemented by the government to reduce poverty in Indonesia is the empowerment of Micro, Small, and Medium Enterprises (MSMEs). The problem is MSMEs in Indonesia find it challenging to develop due to their limited capital. To avoid new problems and overcome public confusion regarding capital, the government launched a micro waqf bank, commonly abbreviated as BWM. Micro waqf bank is a sharia microfinance institution that aims to empower the lower middle class. Micro waqf banks provide capital assistance for the lower middle class, who may need access to formal financial institutions. In addition, micro waqf banks also offers help to their customers. This research aims to understand and learn more about the systematics and development of micro waqf banks in empowering MSMEs in Indonesia. The research method used in this research is descriptive qualitative by collecting data from various secondary sources.